Polymer hole-transport material improving thermal stability of inorganic perovskite solar cells - Mu, Shaiqiang; Ye, Qiufeng; Zhang, Xingwang; Huang, Shihua; You, Jingbi (Frontiers of Optoelectronics (Online), 2020)
Cesium-based inorganic perovskite solar cells (PSCs) are paid more attention because of their potential thermal stability. However, prevalent salt-doped 2,2′,7,7′-tetrakis(N,N-dipmethoxyphenylamine)9,9′-spirobifluorene (Spiro-OMeTAD) as hole-transport materials (HTMs) for a high-efficiency inorganic device has an unfortunate defective thermal stability. In this study, we apply poly (3-hexylthiophene-2,5-diyl) (P3HT) as the HTM and design all-inorganic PSCs with an indium tin oxide (ITO)/SnO 2 /LiF/CsPbI 3− x Br x /P3HT/Au structure. As a result, the CsPbI 3 − x Br x PSCs achieve an excellent performance of 15.84%. The P3HT HTM-based device exhibits good photo-stability, maintaining ∼80% of their initial power conversion efficiency over 280 h under one Sun irradiation. In addition, they also show better thermal stability compared with the traditional HTM Spiro-OMeTAD.